2003
DOI: 10.1074/jbc.m304205200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Instability and Fibrillar Aggregation of Non-expanded Human Ataxin-3 Revealed under High Pressure and Temperature

Abstract: Protein misfolding and formation of structured aggregates are considered to be the earliest events in the development of neurodegenerative diseases, but the mechanism of these biological phenomena remains to be elucidated. Here, we report a study of heat-and pressure-induced unfolding of human Q26 and murine Q6 ataxin-3 using spectroscopic methods. UV absorbance and fluorescence revealed that heat and pressure induced a structural transition of both proteins to a molten globule conformation. The unfolding path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…We found that upon incubation at pH 1.9, the acid-denatured state of Atax3(Q28), or what may be termed the "A state," displayed spectral properties similar to partially folded conformational species induced by pressure, temperature, and denaturant (24,27). Specifically, the A state showed an increased fluorescence signal, increased bis-ANS binding, and a red shift in fluorescence emission maximum ( max ) from 337 nm in the native state to 343 nm in the A state (Figs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that upon incubation at pH 1.9, the acid-denatured state of Atax3(Q28), or what may be termed the "A state," displayed spectral properties similar to partially folded conformational species induced by pressure, temperature, and denaturant (24,27). Specifically, the A state showed an increased fluorescence signal, increased bis-ANS binding, and a red shift in fluorescence emission maximum ( max ) from 337 nm in the native state to 343 nm in the A state (Figs.…”
Section: Resultsmentioning
confidence: 96%
“…Recent work from our laboratory and others have shown that destabilization of the native state of nonpathological variants of ataxin-3 by various stresses such as chemical denaturation and heat can result in the formation of fibrillar aggregates (24,25,27). Based on various results, we and others have proposed that in the pathological state, the elongation of the polyglutamine tract disrupts the stability of the native conformation of the ataxin-3 (19,24).…”
mentioning
confidence: 99%
“…For comparison of ␤-amyloid aggregated peptides (A␤ and A␤ [25][26][27][28][29][30][31][32][33][34][35] ), samples that had been incubated for 4 days at 37°C were deposited onto a CaF 2 plate and the solvent was allowed to evaporate overnight at room temperature. 20 …”
Section: Fourier-transformed Ir Spectroscopymentioning
confidence: 99%
“…Using complementary biophysical techniques including spectroscopic methods and electron microscopy, we have shown that the pressure-induced unfolding of human ataxin-3 (Q26) was characterized by a complex mechanism, implying several steps and unfolding intermediates within the experimental pressure range (23). First, the protein started to unfold in a relatively low-pressure range (P 1/2 = 145 MPa).…”
Section: Pressure-induced Unfolding Of Human Ataxin-3mentioning
confidence: 99%